Nitric oxide in gingival crevicular fluid and nitric oxide synthase expression in the gingiva of patients with sickle cell disease - Esra Güzeldemir (Turkish Journal of Hematology, 2011)
Objective: This study aimed to biochemically measure the production of nitric oxide in gingival crevicular fluid and immunohistochemically measure the expression of inducible nitric oxide synthase in the gingiva of patients with sickle cell disease. Additionally, we aimed to obtain insight into the immunopathology of sickle cell disease by comparing inducible nitric oxide synthase levels in patients with sickle cell disease and controls using gingiva and gingival crevicular fluid. Materials and Methods: The study included 20 sickle cell disease patients and 20 healthy controls. Immunohistochemical analysis was used to measure inducible nitric oxide synthase expression in gingiva and nitric oxide levels in gingival crevicular fluid were spectrophotometrically measured. Results: Nitric oxide levels in the patients and controls did not differ significantly (21.2±4.5 and 23.1±2.3 μM L-1, respectively, p>0.05). There weren’t any statistically significant differences in infiltrated inflammatory cells, density of inflammatory cells that stained with inducible nitric oxide synthase, or nitric oxide expression in gingiva between the patient and control groups (p>0.05). Conclusion: To the best of our knowledge this is the first study to examine the expression of inducible nitric oxide synthase in the gingiva and gingival crevicular fluid in patients with sickle cell disease. Using the gingiva and gingival crevicular fluid we were unable to observe sickle cell disease-associated inducible nitric oxide synthase expression and a difference in nitric oxide levels.